Measuring optic nerve sheath diameter in children: a simple ultrasound protocol for ICP assessment - Zoica, Bogdana Sabina; Chalattil, Bipin (Frontiers in Pediatrics, 2026)
Prompt and accurate detection of elevated intracranial pressure (ICP) is vital in the management of pediatric traumatic brain injury (TBI). While invasive ICP monitoring remains the gold standard, its application is often limited by contraindications or local logistical constraints. Consequently, a substantial number of moderate TBI cases are managed without direct ICP monitoring, despite the risk of secondary intracranial hypertension. This underscores the need for reliable, non-invasive diagnostic alternatives. One such technique—optic nerve sheath diameter (ONSD) measurement via point-of-care ultrasound (POCUS)—leverages cerebrospinal fluid (CSF) accumulation around the retrobulbar optic nerve as a surrogate marker for raised ICP. Although ONSD is recognised for its simplicity, speed, and repeatability, its clinical adoption in pediatric settings remains limited due to the absence of standardised guidelines and normative data. This manuscript synthesises the current evidence on ONSD measurement in children, highlighting its diagnostic potential, methodological considerations, and limitations. By consolidating recent research, we aim to support pediatric intensivists in the practical application of ONSD as a non-invasive tool for ICP assessment, ultimately improving clinical decision-making and prognostic evaluation in pediatric TBI.